STUDI TENTANG NILAI – NILAI SOSIAL BUDAYA DALAM UNDANG (HAEP) PADA UPACARA KEMATIAN - Thobias Fanggi (Universitas Negeri Malang, 2016)
Indonesia has a diverse culture that formed the environment of the community. One culture in Indonesia is culturally Undang (HAEP) at funerals. This culture remains preserved in the district semau. This is done for generations. Culture Undang (HAEP) through several processes including processes is pre-Congress consultations; The authority which sits on top of traditional mats (Nehe Tuan) and Leader of the Council; Means In Deliberation; Results of Deliberation (Determining the time of the tomb, Open mat full or half open, Nukuneo (Bolokai), Mitang Inala, Butu Leng, Amount in Haep (Undang), envoy to Haep (Undang), presence of people) DOI : http://dx.doi.org/10.17977/um019v1i22016p132